Identification and Characterization of a Peptide That Specifically Binds the Human, Broadly Neutralizing Anti-Human Immunodeficiency Virus Type 1 Antibody b12 - Zwick, Michael B. (American Society for Microbiology, 2001)
Human monoclonal antibody (MAb) b12 recognizes a conformational epitope that overlaps the CD-4-binding site of the human immunodeficiency virus type 1 (HIV-1) envelope. MAb b12 neutralizes a broad range of HIV-1 primary isolates and protects against primary virus challenge in animal models. We report here the discovery and characterization of B2.1, a peptide that binds specifically to MAb b12. B2.1 was selected from a phage-displayed peptide library by using immunoglobulin G1 b12 as the selecting agent. The peptide is a homodimer whose activity depends on an intact disulfide bridge joining its polypeptide chains. Competition studies with gp120 indicate that B2.1 occupies the b12 antigen-binding site. The affinity of b12 for B2.1 depends on the form in which the peptide is presented; b12 binds best to the homodimer as a recombinant polypeptide fused to the phage coat. Originally, b12 was isolated from a phage-displayed Fab library constructed from the bone marrow of an HIV-1-infected donor. The B2.1 peptide is highly specific for b12 since it selected only phage bearing b12 Fab from this large and diverse antibody library.